THE IMPACT OF ORGANIZATIONAL COMMITMENTS AND SUPERVISION ON WORK DISCIPLINE of EMPLOYEE of CV. BINTANG TERANG PEKANBARU - Yapentra, Arhipen (Eko dan Bisnis: Riau Economic and Business Review, 2021)
The purpose of the study was to analyze the impact of organizational commitment and supervision on the work discipline of employees of CV. Bintang Terang Pekanbaru with a total population and research sample of 41 respondents. This research uses descriptive and quantitative methods as well as multiple linear regression data analysis techniques. The average score for the overall organizational commitment variable statement was 3.87 and the Supervision variable was 3.90, meaning that both variables are in the GOOD class interval. Based on the results of the multiple linear regression test, the value of t_count for organizational commitment and supervision was greater than t_table with a significance < 0.05 and an F arithmetic value > F table. Thus, Ha was accepted, meaning that organizational commitment and supervision on partially or simultaneously have a positive effect on Work Discipline ofÂ  employees CV Bintang Terang Pekanbaru . The magnitude of the influence of the two variables on work discipline is obtained from the Adjusted R Square value of 0.584 or 58.4% and the remaining 41.6% is influenced by other variables outside of this study